Strategy to Increase Local Original Income of Tanah Laut Regency: Review of Administrative and Legal Aspects of Business - Hairudinor Hairudinor; Abdul Halim Barkatullah; Imam Syafa'i (West Science Interdisciplinary Studies, 2025)
This study analyzes strategies to increase Local Revenue (PAD) in Tanah Laut Regency, South Kalimantan, with a focus on the administrative and legal aspects of business. Using descriptive qualitative methods and secondary data analysis for the 2019-2023 period, this study identifies the main challenges in optimizing PAD and formulates strategies to increase it. The results of the study show that although there was an increase in PAD with a CAGR of 5.6%, its contribution to total regional revenue is still relatively low (average 10.65%). The main recommended strategies include: (1) implementation of a GIS system for mapping tax potential, (2) development of an integrated e-tax system, (3) increasing the capacity of tax human resources, (4) harmonization of Regional Regulations with Law No. 1/2022, and (5) strengthening tax law enforcement. The implementation of this strategy is projected to increase PAD by 25-30% in the medium term (3-5 years).